Guinea : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that in 2003, Guinea's economic situation deteriorated on account of exogenous conditions, as well as poor macroeconomic management and the lack of progress in key structural areas. Annual real GDP growth slowed down from 4.2 percent in 2002 to an estimated 1.2 percent. In the structural reform area, progress was mixed. The outlook for 2004 is plagued by poor performance in the first quarter of the year and by important downside risks, exogenous as well as policy related.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet